Regulation of apoptosis: lessons from Drosophila and their implications for human health and disease - Steller, Hermann (Henry Stewart Talks, 2007)
Many different signals influence apoptosis, "Gas" and "brake" model of apoptosis, Reaper, Hid and Grim, IAPs and cancer, Use of Drosophila, Ubiquitination and apoptosis, diap1, In proliferating tissues, damage induced cell death is compensated by extra growth of the neighboring cells, Evidence for the "active model" of compensatory proliferation, Regulation of caspase activation, Cytochrome c is required for effector caspase activation in Drosophila spermatids, Cyt-c-d and other apoptosome proteins are required for normal developmental apoptosis in the Drosophila retina, Generation of Sept4-null mice, Acquired characteristics of cancer cells